اصول تعليم مهارات اللغة العربية من منظور نظرية فيجو تسكي البنائية الاجتماعية - Prabowo Adi Widayat (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
Learning of Arabic language proficiency is a form of language learning with an emphasis on strengthening communication within the dimensions of the interaction language. Therefore, the concept and implementation of learning of Arabic language proficiency continues to consider aspects of the development of students in a variety of levels, for it required a theoretical idea-based language proficiency learning that includes proficiency listening, speaking, reading, and writing. Social Constructivism is a learning theory proposed by Lev Vygotsky that seeks to emphasize the importance of social interaction and cooperative learning in building depictions on the emergence of cognitive and emotional reality. In theory, the Zone Proximal Development (ZPD) patterns developed as "distance between the actual developmental level, as determined through problem solving that can be tailored to an individual's level of understanding, with the level of potential development, as determined through a problem-solving under adult guidance or in collaboration, through peers" and then, Scaffolding is a technique for changing the level of support which during sessions teaching, a specific expertise which have either teacher or student who has more capabilities in the field of specific studies should be able to adjust the amount of her care with the level of student performance that is used. Key Word, Social Contructivism, Learning of Arabic Language Proficience, Zone Proximal Development (ZPD), Scaffolding